Strategic Roles of Religious Leaders in Shaping Islamic Youth Morality: Peran Strategis Pemuka Agama dalam Pembentukan Akhlak Pemuda Islam - Siregar, Muhammad Naim; Madya, Efi Brata (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Religious and moral challenges among urban Muslim youth are intensifying in the digital era, especially in areas with significant Muslim populations. Specific Background: Medan Denai District faces increasing moral degradation among Islamic youth, despite having many religious institutions. Knowledge Gap: Previous studies have examined the role of religious leaders generally, but none have specifically analyzed their role in Medan Denai using an inverted pyramid framework and integrating digital era challenges. Aims: This study aims to analyze the strategic role of religious leaders in shaping youth morality through the inverted pyramid approach. Results: The findings reveal that religious leaders play fundamental roles through three strategies: digital-era da'wah adaptation, intensive mentoring, and mosque revitalization. These have led to increased youth participation and strengthened moral behavior, although challenges remain regarding social media influence, parental involvement, and institutional synergy. Novelty: This study develops a contextual model of youth moral development based on the inverted pyramid framework adapted to the digital era. Implications: The study highlights the importance of collaborative strategies between religious leaders, families, and institutions to address contemporary moral challenges. Highlight Religious leaders act as moral anchors for youth in urban communities. Inverted pyramid approach builds strong spiritual foundations before behavioral change. Digital da'wah, mentoring, and mosque revitalization strengthen youth moral development. KeywordsReligious Leaders, Youth Morality, Inverted Pyramid Approach, Digital Da'wah, Mentoring Program